Combined inactivation of the SOS response with TCA fumarases and the adaptive response enhances antibiotic susceptibility against Escherichia coli - Murillo-Torres, Marina; Peñalver-Fernández, Isabel María; Quero-Delgado, Marta; Diaz-Diaz, Sara; Romero-Muñoz, María; Recacha, Esther; Docobo-Pérez, Fernando; Rodríguez-Martínez, José Manuel (Frontiers in Microbiology, 2025)
IntroductionTargeting bacterial DNA damage responses such as the SOS response represents a promising strategy for enhancing the efficacy of existing antimicrobials. This study focuses on a recently discovered DNA damage response mechanism involving tricarboxylic acid cycle (TCA) fumarases and the adaptive response, crucial for Escherichia coli survival in the presence of genotoxic methyl methanesulfonate (MMS). We investigated whether this pathway contributes to protection against antibiotics, either separately or in combination with the SOS response.MethodsAn isogenic collection of E. coli BW25113 mutants was used, including strains deficient in fumarases (ΔfumA, ΔfumB, ΔfumC) and the adaptive response (ΔalkA, ΔalkB, ΔaidB). Additional SOS response inactivation (ΔrecA) was conducted by P1 phage transduction. All mutants were subjected to antimicrobial susceptibility testing, growth curve analysis, survival and evolution assays. To validate the relevance of these findings, experiments were also performed in a quinolone-resistant E. coli ST131 clinical isolate.Results and discussionOverall, no significant differences or only moderate increases in susceptibility were observed in the single mutants, with ΔfumC and ΔaidB mutants showing the highest susceptibility. To enhance this effect, these genes were then inactivated in combination with the SOS response by constructing ΔfumC/ΔrecA and ΔaidB/ΔrecA mutants. These combinations exhibited significant differences in susceptibility to various antimicrobials, particularly cephalosporins and quinolones, and especially in the ΔfumC/ΔrecA strain. To further assess these results, we constructed an E. coli ST131 ΔfumC/ΔrecA mutant, in which a similar trend was observed. Together, these findings suggest that co-targeting the SOS response together with fumarases or the adaptive response could enhance the effectiveness of antibiotics against E. coli, potentially leading to new therapeutic strategies.